Pengaruh Tingkat Pendidikan, Pengalaman Kerja, dan Beban Kerja terhadap Kualitas Kerja pada Pegawai Dinas Sosial Kabupaten Sleman - Kusuma Chandra Kirana; Tri Ratna Purnamarini; Rya Febi Mahanani (Universitas Batanghari, 2023)
This study aims to determine the effect of education level, work experience, and workload on the quality of work of employees of the Sleman District Social Service.The population and sample used in the study were all employees of the Sleman Regency Social Service, totaling 60 people using the saturated sample method. Methods of data collection using questionnaires. Processing and analysis of data obtained from questionnaires using SPSS 23.The results of the study showed that there was no positive and not significant effect of the education level variable on the quality of work of Social Service employees in Sleman Regency. There is a positive and significant effect of work experience and workload variables on the work quality variable of Sleman District Social Service employees.